A novel mutation in the SerpinC1 gene presenting as unprovoked neonatal cerebral sinus venous thrombosis in a kindred1. Issue 1 (19th September 2012) - Kumar, Riten; Moharir, Mahendranath; Yau, Ivanna; Williams, Suzan
Abstract Antithrombin (AT) deficiency has been associated with an increased risk of pediatric cerebral sinus venous thrombosis (CSVT); but few cases of neonatal CSVT have been reported. We describe two half‐siblings who presented with seizures in the first week of life and were found to have extensive CSVT with associated parenchymal and intraventricular hemorrhage. Both infants were found to have type 1 AT deficiency. Sequencing of the SerpinC1 gene revealed a novel heterozygous mutation on exon 5 (c.1009C > T p.Q337X). Both infants were treated with anticoagulation and had recanalization of the dural sinuses on follow up imaging. Pediatr Blood Cancer 2013; 60: 133–136. © 2012 Wiley Periodicals, Inc.